Dual Personality and Schizophrenia of Characters in Contemporary Central American Literature - Sun, Junchi (2020)
To approach the subject, two works were chosen, one from Costa Rica and the other from El Salvador. From a literary perspective, they illustrate aspects of the Central American society with problems such as violence, male chauvinism, social repression, and delinquency. Through a comparative study and from the perspective of rhizome theory, proposed by Deleuze and Guatarri, the behavior of the protagonist of each work is analyzed, displaying characteristics of a dual personality or schizophrenia in that society.